Conceptualizing a strategic framework of social responsibility in Islamic economics - Barom, Mohd Nizam (International Islamic University Malaysia, 2013)
In developing Islamic economics as a discipline, its proponents have emphasized on religious and ethical postulations of its economic agents as the essential micro-foundation towards the realization of its normative goals. Nevertheless, recent debates have highlighted the growing frustration on the failure of Islamic finance in addressing ethical and socially responsible issues beyond the legal realm of Shari’ah-compliance. Likewise, the survey of the literature concerning the multiple aspects to individuals’ motivations for the support towards Islamic finance has also revealed mixed results. While the religious aspect has been shown to be a primary concern among the users of Islamic financial services in numerous studies, economic consideration remains an essential component in such decisions and in many instances overwhelmed the normative dimension. Based on these observations, perhaps it is wise to reflect the applicability of Islamic economic theory in the context of the contemporary reality of the Muslim society. In the transitional state where the economic dimension remains as a dominant factor in individuals’ decisions, the crucial challenge is to reconcile self-interest motives with the social interest. One of the prospective means to reduce the potential conflict between the two can be found in the literature of strategic or instrumental theory of ethics. This paper seeks to discuss this issue from an Islamic perspective within the transformative paradigm of Islamic economics. The strategic framework of social responsibility is outlined based on a synthesis of the normative and positive dimensions of human instincts, the notion of falah, the moral and price filters of market and the theory of instrumental ethics. The paper argues that a strategic understanding of social responsibility issues and commitment is not in conflict with Islamic teachings. Nevertheless, it should not be taken as a theory independent of its normative foundation as normally construed in the Western literature. Instead, the strategic theory in Islamic perspective should be seen as complementary in nature with the normative underpinnings as the core, providing additional incentive and motivation for individuals to address social responsibility issues. Additionally, it has also been argued that these normative goals can be facilitated by the presence of an appropriate socio-economic environment. Recognizing that the notions of corporate social responsibility (CSR) and socially responsible investing (SRI) have been often celebrated as a force to tame the vigor of egoistic orientation under Western capitalism, similar ‘institutions’ can also be introduced in the context of an Islamic economy. This should provide additional economic incentive for businesses to address broader social, ethical, and environmental issues, and reinforce further the strategic understanding of social responsibility and its practice among individuals, businesses and the society as a whole.